Juridical Analysis of the Impact of Online Application-Based Public Transportation of Motorcycle Taxis Regulation Policies (Case Study in Tangerang and surrounding areas) - hantoro, setyo; Santoso, Aris Prio; Guntara, Peter (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
It has been more than 14 years since motorized two-wheeled vehicles have been operating on the roads, through the